Integrasi Kebijakan Makroekonomi Dalam Mendorong Pertumbuhan Ekonomi Inklusif Di Indonesia - Nur Ismi D. Litiloly; Natelda R. Timisela (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
Inclusive economic growth is one of the priorities in Indonesia's national development, emphasizing that the benefits of growth should be felt equally by all segments of society. Macroeconomic policies play a crucial role as a tool to achieve these goals thru inflation control, sustainable fiscal management, consistent monetary policy, and public investment plans focused on welfare and food security. This research aims to examine the integration of macroeconomic policies in supporting inclusive economic growth in Indonesia. The method applied is descriptive-qualitative analysis, referring to 20 scientific articles published between 2022 and 2025, which are related to fiscal policy, monetary policy, price stability, income inequality, job creation, and food security. The results of the search indicate that expansionary fiscal policies, particularly thru spending on social needs, infrastructure development, and support for the agricultural sector, can reduce inequality, strengthen food security, and improve public access to various economic opportunities. Consistent monetary policy serves to protect the purchasing power of low-income communities by regulating inflation, maintaining stable food prices, and strengthening the exchange rate, which supports financial stability and creates a more open investment climate. Nevertheless, there are obstacles in coordinating policies, particularly in maintaining a balance between growth, fair distribution, and food security at the national level. Therefore, it can be concluded that the integration of macroeconomic policies is an important factor in accelerating the achievement of inclusive economic growth in Indonesia, and provides recommendations for the government to strengthen cooperation in fiscal, monetary, and food policies.